The Role of Spiritual Intelligence, Emotional Intelligence, and School Principals’ Leadership in Improving Teacher Performance through Work Motivation: A Systematic Literature Review - Dessy Masita; Antoni Tsaputra (Journal of General Education and Humanities, 2026)
This study aims to systematically examine the relationship between spiritual intelligence, emotional intelligence, principal leadership, work motivation, and teacher performance using a Systematic Literature Review (SLR) approach. The SLR method was chosen because it can integrate empirical findings transparently and is replicable. The selection process followed the PRISMA 2016-2026 guidelines, starting with 320 articles identified through the Scopus, ScienceDirect, Emerald, and Google Scholar databases, which were then screened based on inclusion and exclusion criteria, resulting in 32 final articles eligible for analysis. The results of the synthesis indicate that spiritual intelligence contributes to shaping teachers’ intrinsic motivation and professional integrity, while emotional intelligence plays a role in emotion regulation and interpersonal effectiveness, which in turn impact performance. School principal leadership, particularly the transformational style, was found to be the primary external factor driving teachers’ motivation and performance. Work motivation was identified as a key mediating variable bridging the influence of these three factors on teacher performance, as explained within the framework of Self-Determination Theory. The implications of this study emphasize the importance of developing teachers’ spiritual and emotional intelligence, as well as strengthening principals’ leadership capacity, as strategies for the sustainable improvement of educational quality.